2020
DOI: 10.1017/s1041610219001959
|View full text |Cite
|
Sign up to set email alerts
|

The association of eating challenges with energy intake is moderated by the mealtime environment in residential care homes

Abstract: Objectives: Given the increased risk of malnutrition in residential care homes, we studied how specific aspects of the mealtime environment are associated with residents’ eating challenges and energy intake in general and dementia care units of these homes. Design: Cross-sectional study. Participants: 624 residents and 82 dining rooms. Setting: 32 residential care homes across Canada. Measurements: Eating challenges were measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…30 Due to the higher level of evidence provided in this RCT, certainty of evidence for the above outcomes was rated as moderate. Dining room enhancement studies including these outcomes in lower quality studies (and therefore excluded from GRADEpro analysis) reported inconsistent effects on energy and/or protein intake (increased in two studies, 32,42 non-significant change in six studies, 24,[43][44][45][46][47] decreased in two studies 44,45 ) and weight (increased in two studies, 26,32 non-significant or no change in four studies 24,25,35,46 ). One study reported improved quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…30 Due to the higher level of evidence provided in this RCT, certainty of evidence for the above outcomes was rated as moderate. Dining room enhancement studies including these outcomes in lower quality studies (and therefore excluded from GRADEpro analysis) reported inconsistent effects on energy and/or protein intake (increased in two studies, 32,42 non-significant change in six studies, 24,[43][44][45][46][47] decreased in two studies 44,45 ) and weight (increased in two studies, 26,32 non-significant or no change in four studies 24,25,35,46 ). One study reported improved quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the current review, taken in context with a recent review on social connection and mental health outcomes in this population [ 24 ], suggest mechanisms consistent with previously proposed models [ 4 , 77 ], but which highlight specific psychological factors (e.g., stress, depression) and lifestyle (e.g., nutrition, sleep) which warrant further research in this population. For example, with respect to the latter, addressing social connection as a means to improving nutritional status – either through individual-delivered interventions [ 78 ] or addressing aspects of the LTC home mealtime environment [ 79 ] – has been investigated. Third, few studies stratified results to compare populations within LTC homes (e.g., by sex or gender [ 47 49 , 59 ], cognition […”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the idea of tailoring care to the individual resident is prevalent both in broader mealtime care literature ( Reimer & Keller, 2009 ; Slaughter et al, 2020 ; Wu et al, 2018 ) and in dementia care literature ( Fazio et al, 2018 ; Manthorpe and Samsi, 2016b ). This concept also features prominently in guidance and regulation in this area ( Care Quality Commission, 2014 ; Social Care Institute for Excellence, 2020 ).…”
Section: Discussionmentioning
confidence: 99%